Maternal indications, trends, and fetal outcomes of instrument-assisted vaginal deliveries in the United Arab Emirates - Tom, Adhya M.; Prince, Chris M.; Muhammed, Shameema; Sreejith, Anusha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Instrument-assisted vaginal deliveries (IAVDs), using vacuum or forceps, are vital for expediting childbirth in cases such as fetal distress or prolonged labor. While effective in preventing cesarean sections and reducing maternal-fetal morbidity, they carry risks including perineal trauma and neonatal injury. This study assessed the clinical indications and outcomes of IAVDs in a UAE tertiary hospital. Methods: A retrospective review was conducted at Thumbay University Hospital, Ajman, including women who underwent IAVDs between January 2022 and January 2025. Data on maternal demographics, instrument type, clinical indications, and maternal-neonatal outcomes were collected using a validated form. Cesarean deliveries and incomplete records were excluded. Data were analyzed with SPSS v29 using descriptive statistics and Chi-square tests, with significance at p<0.05. Results: Among 116 IAVD cases, most women were primigravida, aged 21-34, and delivered at full term. Indications included poor maternal effort (60.3%), prolonged second stage (39.7%), and fetal distress (37.9%). Vacuum was the predominant instrument. Neonatal outcomes were favorable, with 93.1% of newborns having normal birth weight. Common complications included respiratory distress (19.8%), NICU admission (14.7%), and cephalohematoma (12.9%). Maternal outcomes included episiotomy (82.8%) and vaginal tears (8.6%), with minimal serious complications. Conclusions: IAVDs remain a safe and effective option for managing prolonged labor or fetal compromise. When guided by appropriate clinical judgment and technique, they yield favorable maternal and neonatal outcomes. Emphasis on early recognition of indications, ongoing operator training, and vigilant monitoring can further optimize safety.